Chlorhexidine chemical burn in hand surgery: A case review and recommendations for prevention - Alireza Najafian; Brynn Hathaway; Sven Gunther; Joel S. Solomon (Elsevier, 2022)
Chlorhexidine gluconate (CHG) is one of the most commonly used antiseptic agents for pre-procedural skin preparation and is generally considered safe; however, there are reports that, under certain circumstances, CHG can cause chemical burns. This case report highlights the occurrence and management of a CHG chemical burn in a pediatric patient undergoing upper extremity surgery with a tourniquet despite the use of routine protective measures.